Estratégias competitivas das empresas distribuidoras de gás liquefeito de petróleo - GLP atuantes no estado do Ceará - Miranda, Carlos Henrique de Almeida (2007)
This work’s goal is to analyze the competitive strategies of the LPG (Liquefied Petroleum Gas) in Ceará. It is a strategic sector of the national economy, with a strong regulation from the State, which causes a limitation, in a certain way, in the actions to be developed by the companies of this productive segment. The LPG distributors in Brazil have PETROBRÁS as their main supplier, a company that owns 99% of the LPG production, so, the relationship with the mentioned supplier is the same to all distributors, or, in other words, the gas sold by PETROBRÁS is the same, which a reason to make the competitiveness in this area to be sensed not only by the costs management (costs reduction), but also by the differences (quality, service providing, marketing, aggressiveness, technologic innovations, logistics, etc). The strategy choices that guarantee the competitiveness are one of the most important decisions of the companies that work in this sector, considering the limits imposed by the governmental institutions. The research has an exploratory and describing nature. In what concerns the methodologist aspects, there has been done a field research in the LPG distributors in the State of Ceará, using as collecting tools: the observation, the questionnaire and the interview. The observed results in the two companies that answered the research showed that in one of them, there is a predominance of the strategies that focus the operational excellence, as in the other one, the main strategy is to focus in the client satisfaction. Both of them use a defensive strategies to face the competition.